Socio-economic analysis of lavender crop in Himachal Pradesh - Dhillon, S Singh, S S (Journal of Spices and Aromatic Crops, 2017)
The data collected from 20 lavender growers of three blocks of Chamba district by personal interview using multi-stage purpose sampling technique. In lavender farms share of male labour was found to be more than female labour. Working as daily paid labourers followed by farming, service and business was the main occupation of adult family members. BCR (over total variable cost) as well as BCR (over total cost) was worked out as 3.170 and 0.642 respectively for lavender crop. Family labour income and net income measures per hectare were found to be negative for lavender crop. About 95% and 25% of selected lavender farmers’ responded positively regarding availability of good quality seed/seedlings and disease problem in seed/seedlings respectively, in the initial stage of sowing of lavender crop. Besides, 90% responded that cost of marketing of produce was high, all the respondents were hiring transport to market the produce. Likewise, 65% responded that there is lack of cheap credit from banks for lavender farming. The lack of profitability indicates the need to strengthen R&D work, extension services, training of farmers, establishment of cold storage facilities, and co-operatives farming societies for enhancing prospects of lavender farming.